Characterization of Biodiesel Particle Emission in Trapping and Regeneration Processes on Cordierite Diesel Particulate Filter - Siricholathum, Komkla; Karin, Preechar; Charoenphonphanich, Chinda; Hanamura, Katsunori; Chollacoop, Nuwong (My University, 2015)
As well-known, the diesel engine has the highest thermal efficiency at the same load as compared with internal combustion engine but its disadvantage is particulate matter (PM) emitted to the atmosphere. The studies of this paper were divided into two parts. The first part studied the quantity of PM from the both diesel and biodiesel fuels at 80% load (2400 rpm) by the trapping process on diesel particulate filter (DPF) used in a partial flow dilution tunnel. The second part studied the regeneration process of PM under the flow rate of oxygen and nitrogen gas of 13.5 L/min with 10%, 15%, and 21% of oxygen gas. The result showed that amount of PM from biodiesel fuel was lower around two times than PM from diesel fuel. The duration in regeneration process of biodiesel's PM was shorter than diesel while increasing of oxygen percentage can reduce regeneration time.
Keywords: Biodiesel; Diesel Engine; Diesel particulate filter; Particulate Matter